2021
DOI: 10.1177/0003489420987194
|View full text |Cite
|
Sign up to set email alerts
|

Otolaryngology Resident Wellness, Training, and Education in the Early Phase of the COVID-19 Pandemic

Abstract: Objective: To determine changes in the residency experience early in the COVID-19 pandemic and evaluate wellness measures among otolaryngology residents. Methods: A web-based survey was administered to U.S. otolaryngology residents. Responses to the Shirom-Melamed Burnout Measure (SMBM) and the Generalized Anxiety Disorder-7 scale were recorded along with data on burnout, demographics, wellness, sleep, training, and education. Results: 119 U.S. otolaryngology residents representing 27 of 42 states with otolary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…Chou and colleagues performed a survey of otolaryngology residents and reported that 98.3% of residents had decreased case volume and 43.7% had decreased surgical involvement. 74 Similarly, Murthy et. al's survey found 43% of respondents were not involved in any skull base procedures, even in COVID-19 negative patients, during the onset of the pandemic.…”
Section: Academicsmentioning
confidence: 95%
“…Chou and colleagues performed a survey of otolaryngology residents and reported that 98.3% of residents had decreased case volume and 43.7% had decreased surgical involvement. 74 Similarly, Murthy et. al's survey found 43% of respondents were not involved in any skull base procedures, even in COVID-19 negative patients, during the onset of the pandemic.…”
Section: Academicsmentioning
confidence: 95%
“…One trainee participated in only the N95 arm due to scheduling conflicts and was therefore excluded from paired analyses. The average age of participants was 26.3 years with a standard deviation of 3.42 (range, [20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Pertinent preexisting conditions included mild asthma (8.7%), allergic rhinitis (26.1%), and prior diagnosis of headaches/migraines (30.4%).…”
Section: Demographicsmentioning
confidence: 99%
“…[27][28][29][30] Studies from COVID-19 demonstrate increased mental strain on health care workers, with several highlighting a prevalence of distress, anxiety, and burnout in otolaryngology trainees. 30,31 It is of the utmost importance to take trainee well-being and personal preference into account when choosing mask wear, when N95 and HFR provide similar levels of protection. Our study highlights that HFRs may be associated with an increase in distress and anxiety levels in a population that is already facing alarming rates of burnout.…”
Section: Psychological Impactmentioning
confidence: 99%
“… 57 In web-based surveys, residents reported spending less time in the hospital, decreased clinical duties, lower surgical volume, and having less procedural independence than before the pandemic. 58 , 59 Additionally, 55% of residents felt that the pandemic had a negative impact on their ability to secure a job or fellowship after training. 59 Over time, hybrid models were developed to combine both virtual and in-person education.…”
Section: Introductionmentioning
confidence: 99%
“…68 Some of the highest increases in subspecialty publications were rhinology and laryngology (51% and 72%, respectively). 58 However, other types of research were negatively impacted during the pandemic including the majority of animal studies and clinical trials being halted at its onset. 69 , 70 In a survey of American rhinologists, 36% of 71 respondents reported their otolaryngology research labs were not able to continue employing hired personnel with full salary due to loss of funding.…”
Section: Introductionmentioning
confidence: 99%